A REVIEW OF IMPROVEMENT OF INTERFACIAL TRANSITION ZONE AND ADHERENT MORTAR IN RECYCLED CONCRETE AGGREGATE - Memon, Shazim Ali; Bekzhanova, Zere; Murzakarimova, Aray (MDPI, 2022)
An increasing amount of construction and demolishing waste has made the implementation of recycled concrete aggregate (RCA) a popular topic; RCA can reduce the environmental pollution caused by the construction industry. This paper describes differences in physical, mechanical, and chemical properties between RCA and natural aggregate (NA). For the first time, the methods of interfacial transition zone (ITZ) improvement in RCA, including strengthening through carbonation, incorporation of mineral admixtures, and different mixing approaches, are extensively covered. In addition, the methods used to improve the adherent mortar regions of RCA are covered. This approach makes it possible to demonstrate the impact of different methods on these regions (ITZ and adhered mortar) and overall RCA enhancement. Lastly, a comparison of each of these methods in terms of their effectiveness is presented. The review of several studies concludes that the carbonation treatment method for ITZ and adherent mortar enhancement are the most efficient and sustainable methods compared to others. Summarizing, using RCA instead of NA provides a sustainable solution for the construction industry due to reducing the amount of produced waste and conserving landfill space. Keywords: recycled concrete aggregate; interfacial transition zone (ITZ); recycled concrete; adherent mortar; microstructure
Keywords: recycled concrete aggregate; interfacial transition zone; ITZ; Type of access: Open Access; recycled concrete; adherent mortar; microstructure